(untitled) (Revista Innova Educación, 2023)
The main objective of the study was to develop a pedagogical management strategy to promote inclusive education at Jorgillo Elementary School, first cycle, primary level. The approach is quantitative, since it allowed the collection and analysis of data in numerical and percentage form, which were subsequently represented through tables and graphs. The population included 6 members of the management team, 6 teachers who teach in the first cycle of the Jorgillo Elementary School, 9 students who present Educational Needs with Specific Support (NEAE) associated or not with disability and the 9 families of these students. The methods used included inductive and analytical approaches, and primary and secondary sources of information on the topic of study were used. Among the results, the strategies implemented to support children with SEN, whether or not related to disability, have had a positive impact on their experience at Jorgillo Elementary School. The management team highlighted that the tactics used by teachers in the classroom are motivating for students. As conclusions, Jorgillo Elementary School employs strategies to promote inclusive education, foster respect and tolerance, promote coexistence and participation, stimulate team learning, select appropriate educational materials, and involve families in their children’s education.